Association of depression and sleep quality with frailty: a cross-sectional study in China - Yue Zhang; Ge Yu; Wei Bai; Songyu Wu; Xiaohan Geng; Wangyi Zhang; Yihang Liu; Yujiao Meng; Junling Gao; Wenjun Li; Changgui Kou (Frontiers Media S.A., 2024)
BackgroundWith the rapid growth of global aging, frailty has become a serious public health burden, affecting the life quality of older adults. Depressive symptoms (depression hereafter) and sleep quality are associated with frailty, but the pathways in which sleep quality and depression affect frailty remain unclear.MethodThis cross-sectional study included 1866 community-dwelling older adults. Demographic characteristics and health-related data of them was collected, and we also assessed frailty, depression, and sleep quality. Descriptive statistics were carried out and ordinal logistic regression analysis was used to identify the factors correlated with frailty. Spearman correlation analysis and mediation analysis were employed to assess associations between sleep quality, depression and frailty. Two-sided p < 0.05 was considered as significant.ResultsThe results showed that 4.1% older adults were frail and 31.0% were pre-frail. Ordinal logistic regression showed that age, consumptions of vegetables, exercise, sleep quality, depression, number of chronic diseases, chronic pain, and self-rated health were correlated with frailty. Spearman correlation analysis revealed that frailty was associated with depression and sleep quality. There was a mediation effect that sleep quality was a significant and positive predictor of frailty (total effect = 0.0545, 95% boot CI = 0.0449-0.0641), and depression was a mediator between sleep quality and frailty (mediation effect = 60.4%).ConclusionDepression and poor sleep quality may be early indicators of frailty in older adults. Improving the sleep quality and psychological state of older adults can improve frailty, which is beneficial for healthy aging.